Remote conditioning or erythropoietin before surgery primes kidneys to clear ischemia-reperfusion-damaged cells: a renoprotective mechanism? - Gardner, David S.; Welham, Simon J.M.; Dunford, Louise J.; McCulloch, Thomas A.; Hodi, Zsolt; Sleeman, Philippa; O'Sullivan, Saoirse; Devonald, Mark A.J. (American Physiological Society, 2014)
Acute kidney injury is common, serious with no specific treatment. Ischemia-reperfusion is a common cause of acute kidney injury (AKI). Clinical trials suggest that preoperative erythropoietin (EPO) or remote ischemic preconditioning may have a renoprotective effect. Using a porcine model of warm ischemia-reperfusion-induced AKI (40-min bilateral cross-clamping of renal arteries, 48-h reperfusion), we examined the renoprotective efficacy of EPO (1,000 iu/kg iv.) or remote ischemic preconditioning (3 cycles, 5-min inflation/deflation to 200 mmHg of a hindlimb sphygmomanometer cuff). Ischemia-reperfusion induced significant kidney injury at 24 and 48 h (χ(2), 1 degree of freedom, >10 for 6/7 histopathological features). At 2 h, a panel of biomarkers including plasma creatinine, neutrophil gelatinase-associated lipocalin, and IL-1β, and urinary albumin:creatinine could be used to predict histopathological injury. Ischemia-reperfusion increased cell proliferation and apoptosis in the renal cortex but, for pretreated groups, the apoptotic cells were predominantly intratubular rather than interstitial. At 48-h reperfusion, plasma IL-1β and the number of subcapsular cells in G2-M arrest were reduced after preoperative EPO, but not after remote ischemic preconditioning. These data suggest an intrarenal mechanism acting within cortical cells that may underpin a renoprotective function for preoperative EPO and, to a limited extent, remote ischemic preconditioning. Despite equivocal longer-term outcomes in clinical studies investigating EPO as a renoprotective agent in AKI, optimal clinical dosing and administration have not been established. Our data suggest further clinical studies on the potential renoprotective effect of EPO and remote ischemic preconditioning are justified.